2010
DOI: 10.1177/0960327110361752
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxic effect of mangiferin and changes in antioxidant enzyme levels of Swiss albino mice treated with cadmium chloride

Abstract: Cadmium is an environmental metal toxin implicated in human diseases. Mangiferin (MGN), a naturally occurring glucosylxanthone, is present in Mangifera indica. In this study, the protective role of MGN against cadmium chloride (CdCl2)-induced genotoxicity was studied in Swiss albino mice. Mice were administered with single intra-peritoneal (i.p.) optimal dose of MGN (2.5 mg/kg b.wt.) before treatment with various concentrations of CdCl2 (7, 8, 9, 10 and 11 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 38 publications
5
22
0
Order By: Relevance
“…Previous study indicated that mango peel extract protected cells from DNA damage induced by H 2 O 2 [Kim et al, 2010]. Similar result demonstrated that mangiferin pretreatment signifi cantly reduced the genotoxic and cytotoxic effects induced by CdCl 2 [Viswanadh et al, 2010]. In addition, mango stem bark extract (MSBE) and mangiferin showed cytoprotective effects against oxidative damage and mitochondrial toxicity induced by xenobiotics to human hepatic cells [Tolosa et al, 2013].…”
Section: Discussionsupporting
confidence: 56%
“…Previous study indicated that mango peel extract protected cells from DNA damage induced by H 2 O 2 [Kim et al, 2010]. Similar result demonstrated that mangiferin pretreatment signifi cantly reduced the genotoxic and cytotoxic effects induced by CdCl 2 [Viswanadh et al, 2010]. In addition, mango stem bark extract (MSBE) and mangiferin showed cytoprotective effects against oxidative damage and mitochondrial toxicity induced by xenobiotics to human hepatic cells [Tolosa et al, 2013].…”
Section: Discussionsupporting
confidence: 56%
“…[17] It also exhibits cardioprotective and antigenotoxic properties[18] among others. Some authors have previously reported the presence of xanthones as mangiferin and its analogue (isomangiferin) in Asplenium species such as Asplenium montanum [19] and Asplenium adiantum-nigrum .…”
Section: Discussionmentioning
confidence: 99%
“…Although mangiferin is a well-known antioxidant, the underlying signaling mechanisms are not fully understood. Nonetheless, it has been reported that mangiferin can enhance the expression of many detoxification and antioxidant enzymes, including NQO1, glutathione-S-transferase (GST), superoxide dismutase (SOD), catalase (CAT), heme oxygenase-1 (HO-1), and uridine 5'-diphosphate-glucuronosyl transferase (UDP-GT) [23][24][25][26] . Nrf2-ARE signaling is a major mechanism in the cellular defense against oxidative or electrophilic stress and controls the gene and protein expression of several types of detoxification and antioxidant enzymes [4] .…”
Section: Discussionmentioning
confidence: 99%